(untitled) (Revista Innova Educación, 2023)
Entrepreneurs are those who revolutionize the world with their ideas. This paper explores the importance of developing entrepreneurial skills in high school students from an Ecuadorian city to stimulate business ideas with an innovative approach. The methodology was based on a descriptive qualitative-quantitative approach. The analytical method was used, through the survey and interview techniques. The population consisted of 360 students with a probabilistic sample of 202 students from the "Paquisha" and "Emilio Bowen Roggiero" Educational Units and 2 area directors of the Entrepreneurship and Management subject. The results show that in the subject under study, teachers use as a traditional teaching method such as lectures and group work for the development of the business plan, motivated by an educational infrastructure with limitations for the use of digital tools in favor of the innovative entrepreneurship. It is concluded that the implemented methods do not stimulate the development of leadership, teamwork and problem-solving skills in the participating student population.